Prenylated indole-terpenoids with antidiabetic activities from Penicillium sp. HFF16 from the rhizosphere soil of Cynanchum bungei Decne - Liu, Xijin; Kong, Fandong; Xiao, Na; Li, Xiaoyu; Zhang, Mingyu; Lv, Fujin; Liu, Xiaolin; Kong, Xiangchuan; Bi, Jing; Lu, Xinyi; Kong, Daqing; Hao, Gangping; et al. (Frontiers in Microbiology, 2023)
Finding novel and effective suppression of hepatic glucagon response anti-diabetic compounds is urgently required for the development of new drugs against diabetes. Fungi are well known for their ability to produce new bioactive secondary metabolites. In this study, Four new prenylated indole-terpenoids (1-4), named encindolenes I-L, as well as a known analogue (5), were isolated from the fungus Penicillium sp. HFF16 from the rhizosphere soil of Cynanchum bungei Decne. The structures of the compounds were elucidated by spectroscopic data and ECD analysis. In the antidiabetic activity assay, compounds 1-5 could inhibit glucagon-induced hepatic glucose output with EC50 values of 67.23, 102.1, 49.46, 25.20 and 35.96 μM, respectively, and decrease the intracellular cAMP contents in primary hepatocytes.